Design, synthesis and structure of novel G-2 melamine-based dendrimers incorporating 4-(n-octyloxy)aniline as a peripheral unit - Morar, Cristina; Lameiras, Pedro; Bende, Attila; Katona, Gabriel; Gál, Emese; Darabantu, Mircea (Beilstein Journal of Organic Chemistry, 2018)
Background: 4-(n-Octyloxy)aniline is a known component in the elaboration of organic materials with mesogenic properties such as N-substituted Schiff bases, perylene bisimide assemblies with a number of 2-amino-4,6-bis[4-(n-octyloxy)phenylamino]-s-triazines, amphiphilic azobenzene-containing linear-dendritic block copolymers and G-0 monomeric or dimeric dendritic liquid crystals with photochromic azobenzene mesogens. The present ab initio study explores a previously unknown use of 4-(n-octyloxy)aniline in the synthesis, structure and supramolecular behaviour of new dendritic melamines.Results: Starting from 4-(n-octyloxy)aniline, seven G-2 melamine-based dendrimers were obtained in 29–79% overall yields. Their iterative convergent- and chemoselective synthesis consisted of SN2-Ar aminations of cyanuric chloride and final triple N-acylations and Williamson etherifications (→ G-2 covalent trimers) or stoichiometric carboxyl/amino 1:3 neutralisations (→ G-2 ionic trimers). These transformations connected G-1 chloro- and amino-termini dendrons to m-trivalent cores (triazin-2,4,6-triyl and benzene-1,3,5-triyl units) or tripodands (central building blocks), such as N-substituted melamines with 4-hydroxyphenyl or phenyl-4-oxyalkanoic motifs. Owing to the diversity of cores and central building blocks, the structural assortment of the dendritic series was disclosed by solvation effects (affecting reactivity), rotational stereodynamism and self-organisation phenomena (determining a vaulted and/or propeller macromolecular shape in solution). DFT calculations (in solution), (VT) NMR and IR (KBr) spectroscopy supported these assignments. TEM analysis revealed the ability of the title compounds towards self-assembling into homogeneously packed spherical nano-aggregates.Conclusions: The (non)covalent synthesis and step-by-step structural elucidation of novel G-2 melamine dendrimers based on 4-(n-octyloxy)aniline are reported. Our study demonstrates the crucial influence of the nature (covalent vs ionic) of the dendritic construction in tandem with that of its central building blocks on the aptitude of dendrimers to self-organise in solution and to self-assembly in the solid state.
Keywords: amination; dendrimers; melamines; nano-aggregates; 4-(n-octyloxy)aniline

(untitled) - Zhang, W.; Simanek, E. E. (Org. Lett., 2000)

(untitled) - Takagi, K.; Hattori, T.; Kunisada, H.; Yuki, Y. (J. Polym. Sci., Part A: Polym. Chem., 2000)

(untitled) - Zhang, W.; Nowlan, D. T.; Thomson, L. M.; Lackowski, M. W.; Simanek, E. E. (J. Am. Chem. Soc., 2001)

(untitled) - Steffensen, M. B.; Simanek, E. E. (Angew. Chem., Int. Ed., 2004)
Angew. Chem. 2004, 39, 5290–5292. doi:10.1002/ange.200460031

(untitled) - Hollink, E.; Simanek, E. E. (Org. Lett., 2006)

(untitled) - Lim, J.; Mintzer, M. A.; Perez, L. M.; Simanek, E. E. (Org. Lett., 2010)

(untitled) - Chen, H.-T.; Neerman, M. F.; Parrish, A. R.; Simanek, E. E. (J. Am. Chem. Soc., 2004)

(untitled) - Neerman, M. F.; Zhang, W.; Parrish, A. R.; Simanek, E. E. (Int. J. Pharm., 2004)

(untitled) - Lim, J.; Simanek, E. E. (Mol. Pharmaceutics, 2005)

(untitled) - Merkel, M. O.; Mintzer, M. A.; Sitterberg, J.; Bakowsky, U.; Simanek, E. E.; Kissel, T. (Bioconjugate Chem., 2009)

(untitled) - Lim, J.; Simanek, E. E. (Adv. Drug Delivery Rev., 2012)

(untitled) - Simanek, E. E.; Enciso, A. E.; Pavan, G. M. (Expert Opin. Drug Discovery, 2013)

(untitled) - Zhang, W.; Gonzalez, S. O.; Simanek, E. E. (Macromolecules, 2002)

(untitled) - Acosta, E. J.; Deng, Y.; White, G. N.; Dixon, J. B.; McInnes, K. J.; Senseman, S. A.; Frantzen, A. S.; Simanek, E. E. (Chem. Mater., 2003)

(untitled) - Acosta, E. J.; Gonzalez, S. O.; Simanek, E. E. (J. Polym. Sci., Part A: Polym. Chem., 2005)

(untitled) - Yoo, Y.; Lunn, D. J.; Gonzalez, S.; Ristich, J. A.; Simanek, E. E.; Shantz, F. D. (Chem. Mater., 2006)

(untitled) - Lalwani, S.; Venditto, V. J.; Chouai, A.; Rivera, E. G.; Shaunak, S.; Simanek, E. E. (Macromolecules, 2009)

Dendrimer Chemistry: Concepts, Syntheses, Properties, Applications - Vögtle, F.; Richardt, G.; Werner, N. (Wiley-VCH Verlag GmbH & Co. KGaA, 2009)

(untitled) - Lai, L.-L.; Wang, L.-Y.; Lee, C.-H.; Lin, Y.-C.; Cheng, K.-L. (Org. Lett., 2006)

(untitled) - Lai, L.-L.; Lee, C.-H.; Wang, L.-Y.; Cheng, K.-L.; Hsu, H.-F. (J. Org. Chem., 2008)

(untitled) - Lai, L.-L.; Wang, S.-W.; Cheng, K.-L.; Lee, J.-J.; Wang, T.-H.; Hsu, H.-F. (Chem. – Eur. J., 2012)

(untitled) - Beltrán, E.; Serrano, J. L.; Sierra, T.; Giménez, R. (Org. Lett., 2010)

(untitled) - Yagai, S.; Usui, M.; Seki, T.; Murayama, H.; Kikkawa, Y.; Uemura, S.; Karatsu, T.; Kitamura, A.; Asano, A.; Seki, S. (J. Am. Chem. Soc., 2012)

(untitled) - Shi, Z.; Lu, H.; Chen, Z.; Cheng, R.; Chen, D. (Polymer, 2012)

(untitled) - Kim, D.-Y.; Lee, S.-A.; Choi, Y.-J.; Hwang, S.-H.; Kuo, S.-W.; Nah, C.; Lee, M.-H.; Jeong, K.-U. (Chem. – Eur. J., 2014)

(untitled) - Okuno, T.; Izuoka, A.; Ito, T.; Kubo, S.; Sugawara, T.; Sato, N.; Sugawara, Y. (J. Chem. Soc., Perkin Trans. 2, 1998)

(untitled) - López de Murillas, D.; Piñol, R.; Ros, M. B.; Serrano, J. L.; Sierra, T.; de la Fuente, M. R. (J. Mater. Chem., 2004)

(untitled) - Li, W.; Bu, W.; Li, H.; Wu, L.; Lib, M. (Chem. Commun., 2005)

(untitled) - Jeong, M. J.; Park, J. H.; Lee, C.; Chang, J. Y. (Org. Lett., 2006)

(untitled) - Pintea, M.; Fazekas, M.; Lameiras, P.; Cadis, I.; Berghian, C.; Silaghi-Dumitrescu, I.; Popa, F.; Bele, C.; Plé, N.; Darabantu, M. (Tetrahedron, 2008)

(untitled) - Popa, F.; Lameiras, P.; Moldovan, O.; Tomoaia-Cotisel, M.; Hénon, E.; Martinez, A.; Sacalis, C.; Mocanu, A.; Ramondenc, Y.; Darabantu, M. (Tetrahedron, 2012)

(untitled) - Moldovan, O.; Lameiras, P.; Nagy, I.; Opruta, T.; Popa, F.; Antheaume, C.; Ramondenc, Y.; Darabantu, M. (Tetrahedron, 2013)

(untitled) - Moldovan, O.; Nagy, I.; Lameiras, P.; Antheaume, C.; Sacalis, C.; Darabantu, M. (Tetrahedron: Asymmetry, 2015)

(untitled) - Lates, V.; Gligor, D.; Darabantu, M.; Muresan, L. M. (J. Appl. Electrochem., 2007)

(untitled) - Deac, A. R.; Morar, C.; Turdean, G. L.; Darabantu, M.; Gál, E.; Bende, A.; Muresan, L. M. (J. Solid State Electrochem., 2016)

(untitled) - Morar, C.; Turdean, G. L.; Bende, A.; Lameiras, P.; Antheaume, C.; Muresan, L. M.; Darabantu, M. (C. R. Chim., 2017)

(untitled) - Newkome, G. R.; Yao, Z.; Baker, G. R.; Gupta, V. K. (J. Org. Chem., 1985)

(untitled) - Hernandez, B. A.; Chang, V.; Villanueva, I.; Heagy, M. D. (J. Org. Chem., 1999)

(untitled) - Ricken, S.; Osinski, P. W.; Eilbracht, P.; Haag, R. (J. Mol. Catal. A: Chem., 2006)

U.S. Patent - Negoro, M.; Kawata, K. (Process for Producing 2,4,6-Tris(hydroxyphenylamino)-1,3,5-triazines and 2,4,6-Tris(substituted phenylamino)-1,3,5-triazines, 2005)

(untitled) - de Hoog, P.; Gamez, P.; Driessen, W. L.; Reedijk, J. (Tetrahedron Lett., 2002)

(untitled) - Morar, C.; Cost, L.; Lameiras, P.; Antheaume, C.; Darabantu, M. (Synth. Commun., 2015)

(untitled) - Katritzky, A. R.; Oniciu, D. C.; Ghiviriga, I.; Barkock, A. (J. Chem. Soc., Perkin Trans. 2, 1995)

(untitled) - Katritzky, A. R.; Ghiviriga, I.; Steel, P. G.; Oniciu, D. C. (J. Chem. Soc., Perkin Trans. 2, 1996)

(untitled) - Ghiviriga, I.; Oniciu, D. C. (Chem. Commun., 2002)

(untitled) - Fazekas, M.; Pintea, M.; Lameiras, P.; Lesur, A.; Berghian, C.; Silaghi-Dumitrescu, I.; Plé, N.; Darabantu, M. (Eur. J. Org. Chem., 2008)

(untitled) - Moreno, X. K.; Simanek, E. E. (Macromolecules, 2008)

(untitled) - Bhat, H. R.; Singh, U. P.; Gahtori, P.; Ghosh, S. K.; Gogoi, K.; Prakash, A.; Singh, R. K. (New J. Chem., 2013)

(untitled) - Bhat, H. R.; Singh, U. P.; Gahtori, P.; Ghosh, S. K.; Gogoi, K.; Prakash, A.; Singh, R. K. (RSC Adv., 2013)

(untitled) - Enciso, A. E.; Ramirez-Crescencio, F.; Zeiser, M.; Redón, R.; Simanek, E. E. (Polym. Chem., 2015)

(untitled) - Zhao, Y.; Truhlar, D. G. (Theor. Chem. Acc., 2008)

(untitled) - Weigend, F.; Ahlrichs, R. (Phys. Chem. Chem. Phys., 2005)

Gaussian 09, Revision D.01 (Gaussian, Inc., 2009)

(untitled) - Tomasi, J.; Mennucci, B.; Cammi, R. (Chem. Rev., 2005)

(untitled) - Marenich, A. V.; Cramer, C. J.; Truhlar, D. G. (J. Phys. Chem. B, 2009)

(untitled) - Foster, J. P.; Weinhold, F. (J. Am. Chem. Soc., 1980)

(untitled) - Reed, A. E.; Weinstock, R. B.; Weinhold, F. (J. Chem. Phys., 1985)

(untitled) - de Gennes, P. G.; Hervet, H. (J. Phys., Lett., 1983)

(untitled) - Tomalia, D. A. (Aldrichimica Acta, 2004)

Basic One- and Two Dimensional NMR Spectroscopy - Friebolin, H. (VCH Verlagsgesellschaft, 1991)

Stereochemistry of the Organic Compounds - Eliel, E. L.; Wilen, H. S. (John Wiley & Sons, 1994)

(untitled) - Kessler, H. (Angew. Chem., Int. Ed. Engl., 1982)
Angew. Chem. 1982, 94, 509–520. doi:10.1002/ange.19820940705

(untitled) - Fedeli, E.; Hernández-Aínsa, S.; Lancelot, A.; González-Pastor, R.; Calvo, P.; Sierra, T.; Serrano, J. L. (Soft Matter, 2015)

(untitled) - Stewart, W. E.; Siddall, T. H. (Chem. Rev., 1970)

Applications of Infrared Spectroscopy in Biochemistry, Biology and Medicine - Parker, F. S. (Plenum Press, 1971)

Identification Spectrométrique de Composés Organiques - Silverstein, R. M.; Webster, F. X.; Kiemle, D. J. (De Boeck & Larcier s.a., 2007)

(untitled) - Heacock, R. A.; Marion, L. (Can. J. Chem., 1956)

Cationic Polymers in Regenerative Medicine - Simanek, E. E.; Enciso, A. E. (CHAPTER 10 Cationic Triazine Dendrimers: Synthesis, Characterization, and Biological Applications, 2015)

(untitled) - van Dongen, M. A.; Orr, B. G.; Banaszak Holl, M. M. (J. Phys. Chem. B, 2014)

(untitled) - Alvarez, S. (Dalton Trans., 2013)

Natural Polymer Drug Delivery Systems - Bhatia, S. (Nanoparticles types, classification, characterization, fabrication methods and drug delivery applications, 2016)

(untitled) - Hunter, C. A.; Sanders, J. K. M. (J. Am. Chem. Soc., 1990)